2014
DOI: 10.4085/1062-6050-49.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Limb Range-of-Motion and Humeral-Retrotorsion Adaptation in Collegiate Baseball and Softball Position Players

Abstract: Context: Biomechanically, the motions used by baseball and softball pitchers differ greatly; however, the throwing motions of position players in both sports are strikingly similar. Although the adaptations to the dominant limb from overhead throwing have been well documented in baseball athletes, these adaptations have not been clearly identified in softball players. This information is important in order to develop and implement injury-prevention programs specific to decreasing the risk of upper extremity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 27 publications
1
65
0
Order By: Relevance
“…29 Baseball players tend to present with increased humeral retrotorsion on the dominant arm, because repetitive torsional load on their throwing arm while playing youth baseball, interfere with the rewinding process, causing it to remain more “twisted” relative to the non-dominant arm. 11, 12 Previous studies suggest that increased humeral retrotorsion on the dominant limb protects pitchers from shoulder injuries, 26 but increases the risk of elbow injuries in college 24 and professional 26 baseball pitchers. Although the mechanistic link is still unclear, the effect of dominant humeral retrotorsion on injury risk is likely attributed to the way humeral retrotorsion affects shoulder ROM, 3, 23 and thereby loads at shoulder and elbow joints.…”
Section: Discussionmentioning
confidence: 99%
“…29 Baseball players tend to present with increased humeral retrotorsion on the dominant arm, because repetitive torsional load on their throwing arm while playing youth baseball, interfere with the rewinding process, causing it to remain more “twisted” relative to the non-dominant arm. 11, 12 Previous studies suggest that increased humeral retrotorsion on the dominant limb protects pitchers from shoulder injuries, 26 but increases the risk of elbow injuries in college 24 and professional 26 baseball pitchers. Although the mechanistic link is still unclear, the effect of dominant humeral retrotorsion on injury risk is likely attributed to the way humeral retrotorsion affects shoulder ROM, 3, 23 and thereby loads at shoulder and elbow joints.…”
Section: Discussionmentioning
confidence: 99%
“…Internal derangement (eg, rotator cuff tears, tendinopathy, and labral tears) and osteoarthritis (OA) are not pathologies typically associated with a young healthy athlete, but the occurrence of shoulder injuries or www.journalchiromed.com instability in overhead-throwing sports, such as baseball, softball, volleyball, tennis, or football, is increasingly prevalent. [1][2][3][4][5][6] The rotator cuff and other muscles are dynamic stabilizers, whereas the glenoid labrum, glenohumeral ligaments, joint capsule, and osseous structures are the static stabilizers of the glenohumeral joint. 7 Diagnosis of rotator, labral, or osseous pathologies of the shoulder can be obtained with a variety of imaging modalities, but which structures are best seen, by which modality, has been a topic of ongoing controversy.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,10 Interestingly, these adaptations, which may result in deficits in either internal or external rotation (or both), have been identified as risk factors for upper extremity injury. 2,10,11,19,20 Investigators 5,7,[21][22][23][24][25][26][27][28][29] have demonstrated that osseous adaptions may account for a larger part of the adaptations observed in internal-rotation deficits and external-rotation gains in the overhead-throwing shoulder. In fact, research-ers 5,30,31 have reported that decreases in humeral torsion (HT) accounted for internal-rotation deficits of the glenohumeral joint.…”
mentioning
confidence: 99%